Water incorporated in agricultural production: Water balance considerations - de Toledo Peres, Renato [UNESP]; de Souza, José Gilberto [UNESP] (Springer Nature, 2016)
The international market for food and non-food agricultural products is growing rapidly, as is the concentration of production that takes place at sectoral level due to merger and acquisition processes and the consolidation of spatial monopolies due to regional productive specialization, company consolidation, and intense competition patterns. These processes have a particularly great impact on the primary sectors of the economy, contributing to what is called the commoditization of agriculture, and in this respect, Brazil stands as a unique example. Big corporations aim to achieve the highest possible productivity in order to maximize profits. To this end, water, one of the most basic resources in agricultural production, is exploited to the extreme. An example of this is the use of deepwater aquifers as a major source of water for irrigation. These sources of water, which should be prioritized as strategic reserves, have often shown signs of depletion and scarcity in various key intensive farming areas of Brazil. The dynamics of water exploitation in such cases is what links the two processes examined in this text. First, the authors examine the effective use of resources in irrigated production from free or confined aquifers. Second, the study examines production standards arising from the concept of virtual water export and the use of green, blue, and grey water types. Demand for all these types of water is established in production processes, but there is also an effective extraction of the physical water reserves for incorporation into agricultural products, which we call consumptive use, and, consequently, for the material export of water. These two processes-namely consumptive and non-consumptive uses of water-play an important role in the hydrological cycle and need to be reflected in a new water balance model.